Moralitas, Bisnis dan Penegakan Hukum di Indonesia - Liliana Tedjosaputro (Fakultas Hukum Universitas Islam Indonesia, 2000)
This article discusses the vivid correlation between morality and law enforcement of the business doers. The morality constitutes an important component in managing business. It is considered very important in relations to the business target, and this is consecuted by applying it appropriately on the basis of the situation and existing legal norms.